Clinical parameters, histological analysis, and laser Doppler flowmetry of different subepithelial connective tissue grafts - Eustachio, Ricardo; Ferreira, Rafael; Brondino, Nair; Damante, Carla; De Rezende, Maria; Sant'Ana, Adriana; Greghi, Sebastiaõ; Zangrando, Mariana (Wolters Kluwer, 2018)
Subepithelial connective tissue graft (SCTG) presents favorable outcomes. However, the harvesting technique can influence the anatomical and histological composition of the SCTG. Within the limitations of a case report, the behavior of SCTGs removed by two techniques was evaluated bilaterally in one patient using double blade scalpel (DBS) and de-epithelialized graft (DE). Clinical parameters, laser Doppler flowmetry (LDF) and histological analysis were assessed. Complete root coverage was observed bilaterally, as well as improvement in width and thickness of keratinized tissue 2 years postoperatively. The LDF analysis demonstrated better revascularization in the DBS recipient area compared to DE. The histological evaluation showed differences in tissue composition and organization of collagen fibers. Similar clinical outcomes were observed bilaterally, nevertheless greater morbidity and aesthetic was reported in the DE harvesting area.
Keywords: Connective tissue; histology comparative; laser-Doppler flowmetry; tissue harvesting